2(g+5)=3(2g-1)

Simple and best practice solution for 2(g+5)=3(2g-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(g+5)=3(2g-1) equation:



2(g+5)=3(2g-1)
We move all terms to the left:
2(g+5)-(3(2g-1))=0
We multiply parentheses
2g-(3(2g-1))+10=0
We calculate terms in parentheses: -(3(2g-1)), so:
3(2g-1)
We multiply parentheses
6g-3
Back to the equation:
-(6g-3)
We get rid of parentheses
2g-6g+3+10=0
We add all the numbers together, and all the variables
-4g+13=0
We move all terms containing g to the left, all other terms to the right
-4g=-13
g=-13/-4
g=3+1/4

See similar equations:

| 5x-(2x-5)=x+1 | | 6f+3=4f-11 | | (2k+1)/(3+k)=-1 | | 92+x-152=175 | | 5(x+16)+7x=128 | | 5x+2+2x=12-3 | | 2k+1=-1 | | 3=8r+23 | | 5t+1=14 | | -3+x/3=3 | | 40+6m=5 | | 3x*x-5x-40=0 | | 6p+18=9p-3 | | 9^(3n)=27^(n+2) | | 42=6(y+10) | | v=2*2.5/0.3E+1 | | (2x+4)/2=120 | | 6x+114=16x-6 | | 2(-4-3x)-3x=2(2x+3)-2 | | 4p-2=12+p | | 17=4x-5 | | 20x-8=10x-3 | | X+y=182 | | 2x+(x-1)=92 | | 5x(3×-1)=100 | | 30x+15(140-x)=3360 | | 800=100(2)x | | x14=70 | | 3x-(x-1)=33 | | X=x-1.24=2.69 | | 6g+8=-58 | | 2.2=z=57 |

Equations solver categories